Effects of Flotation-REST on Muscle Tension Pain - Anette Kjellgren; Ulf Sundequist; Torsten Norlander; Trevor Archer (Pain Research and Management)
The purpose of the present study was to investigate whether the floating form of the restricted environmental stimulation technique (REST) may be applied within the field of pain relief. Flotation-REST consists of a procedure whereby an individual is immersed in a tank filled with water of an extremely high salt concentration. Thirty-seven patients (14 men and 23 women) suffering from chronic pain consisting of aching muscles in the neck and back area participated in the study. They were randomly assigned to either a control group (17 participants) or an experimental group (20 participants). The experimental group received nine opportunities to use the flotation-REST technique in the water tank over a three-week period. The results indicated that the most severe perceived pain intensity was significantly reduced, whereas low perceived pain intensity was not influenced by the floating technique. Further, the results indicated that circulating levels of the noradrenaline metabolite 3-methoxy-4-hydroxyphenylethyleneglycol were reduced significantly in the experimental group but not in the control group following treatment, whereas endorphin levels were not affected by flotation. Flotation-REST treatment also elevated the participants' optimism and reduced the degree of anxiety or depression; at nighttime, patients who underwent flotation fell asleep more easily. The present findings describe possible changes, for the better, in patients presenting with chronic pain complaints.